Inovasi Popcorn Jagung sebagai Strategi Membangun Jiwa Kewirausahaan Mahasiswa dalam PKKM - Hamid, Abdurahman; Saputra, Andika; Satrina, Satrina; Ummat, Khaeratul; Anwar, Nur Inayah (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2025)
In the modern era, students are expected not only to excel academically but also to develop a strong entrepreneurial spirit. Innovation plays a crucial role in addressing economic challenges by creating job opportunities and driving sustainable economic growth. The Kampus Merdeka Competition Program (PKKM) serves as a platform for students to enhance their entrepreneurial skills through innovation based on local potential. One promising business opportunity is the innovation of popcorn made from corn, a widely cultivated crop in Indonesia that remains limited to conventional products. PopCrunch is introduced as an innovative solution featuring unique flavors, attractive packaging, and a digital marketing strategy targeting young consumers. This article explores how popcorn can serve as an effective means to foster entrepreneurship among students through PKKM, while also analyzing its business potential to inspire students in establishing small businesses with promising growth prospects.